Makna Khataman al-Qur’an Kamis Legi: Studi Living Qur’an di Pondok Pesantren al-Baqoroh Lirboyo Kota Kediri - Maula, Nabila An'imatul; Rahmawati, Yuliana Desi (Canonia Religia, 2023)
This article aims to examine the tradition of Thursday Legi Quranic Khatam at the Al-Baqoroh Islamic Boarding School for Girls in Kediri City. This research is a field study that uses a qualitative research approach. In this study, the author employs the interpretative anthropology theory of Clifford Geertz. The research results are summarized as follows:Firstly, the tradition of Quranic Khatam at the Al-Baqoroh Islamic Boarding School for Girls in Kediri City is initiated by alumni with the purpose of strengthening the bonds of friendship with the school's caretakers and among alumni, as well as assisting alumni in maintaining and improving their Quranic recitation and memorization. The Quranic Khatam is recited collectively and is divided into portions that are assigned to different participants. The research results indicate that the practices in the Quranic Khatam activity include reciting tawassul (supplication seeking the intercession of holy figures) to the scholars of Lirboyo and ancestors, followed by the Quranic Khatam itself, a closing supplication for the completion of the Quran, slow and deliberate recitation (tartil), recitation of Quranic blessings and the Busyro blessing, recitation of beautiful supplications (mauidhah hasanah), and the conclusion. Alumni have different interpretations of the Thursday Legi Quranic Khatam activity. Some of the meanings attributed to it by alumni include it being a form of service to the scholars of Lirboyo, a way to strengthen bonds of friendship, a means to encourage goodness, and a motivation for alumni to improve their Quranic recitation and memorization. [Artikel ini bertujuan untuk mengkaji tradisi khataman al-Qur’an Kamis Legi yang ada di Pesantren Putri al-Baqoroh Kota Kediri. pertanyaan penelitian yang diajukan berkenaan dengan bagaimana pelaksanaan khataman Kamis Legi di Pesantren Putri al-Baqoroh Kota Kediri? dan bagaimana pemaknaan para jamaah terhadap keberlangsung praktik ini?. lPenelitian ini merupakan penelitian lapangan yang menggunakan pendekatan metode kualitatif. Dalam penelitian ini penulis menggunakan teori antropologi interpretatif Cliffort Geerzt. Adapun hasil penelitian dirumuskan dalam poin berikut: pertama, tradisi khataman al-Qur’an yang ada di Pondok Pesantren Putri al-Baqoroh Kota Kediri yang diprakarsai oleh para alumni dengan tujuan untuk mempererat tali silaturahmi dengan pengasuh dan antar alumni serta untuk membantu para alumni dalam menjaga dan memperbaiki bacaan serta hafalan al-Qur’an. Khataman al-Qur’an dibaca dengan bi al-ghaib dan bi al-naz}ar yang sebelumnya telah dibagi. Rangkaian prosesi acara meliputi: pembacaan tawasul kepada para masyayikh Lirboyo dan leluhur, dilanjutkan dengan khataman al-Qur’an dan do’a khatm al-Qur’an, tartilan, pembacaan shalawat Qur’aniyyah dan Shalawat Busyro, mauidhah hasanah dan penutup. Kedua, pemaknaan alumni terhadap kegiatan khataman al-Qur’an Kamis Legi berbeda-beda. Makna khataman al-Qur’an Kamis Legi yang dikemukakan alumni diantaranya merupakan salah satu bentuk khidmah kepada masyayikh Lirboyo, mempererat silaturahmi, sebagai sarana untuk mengajak kepada kebaikan dan sebagai motivasi para alumni untuk memperbaiki bacaan dan hafalan al-Qur’an.]